Bentuk Kelembagaan Dan Dampak Pemberdayaan Masyarakat Melalui Pemanenan Madu Hutan (Apis Dorsata) Di Taman Nasional Ujung Kulon - Ramawati .; Sulistya Ekawati; Dewi Ratna Kurniasari (Jurnal Analisis Kebijakan Kehutanan, 2022)
National Park Management is faced with conflicts of interest in conservation and community economics. A partnership is one of the answers to this problem. The study was conducted in the buffer area of Ujung Kulon National Park involving 17 respondents who were selected by purposive sampling. The results showed that the communities involved in the partnership gained legal access to harvest wild honey in forest areas, as well as ease of market access and decent prices. The partnership pattern builds awareness of farmer groups to maintain forest sustainability. They realize that if the forest is maintained, it will increase the wild honey harvest and their income.